Comparison of biodegradable and newer generation durable polymer drug-eluting stents with short-term dual antiplatelet therapy: a systematic review and Bayesian network meta-analysis of randomized trials comprising of 43,875 patients - Chong, Bryan; Goh, Rachel Sze Jen; Kong, Gwyneth; Sim, Faith Ruo En; Ng, Chen Han; Teo, Xin Yi Vanessa; Quek, Jing Xuan; Lim, Oliver; Chin, Yip Han; Chan, Siew-Pang; Chan, Mark Y.; Tan, Huay-Cheem; et al. (Journal of thrombosis and thrombolysis, 2022)
Newer generation durable polymer drug-eluting stents (DP-DES) and biodegradable polymer DES (BP-DES) have similar efficacy with dual-antiplatelet therapy (DAPT) duration of > 6 months. However, this difference in outcomes have not been well studied in shorter DAPT regime. This study compares the safety and efficacy profiles of DP-DES and BP-DES based on short-term (1–3 months), intermediate-term (4–6 months) and standard DAPT (6–12 months) durations. A search was conducted on Embase and Medline for Randomized Controlled Trials (RCTs) comparing stent types, and DAPT durations. Primary endpoints include cardiac death, myocardial infarction (MI), definite stent thrombosis, stroke, target vessel revascularization (TVR) and major bleeding. Network analysis was conducted to summarize the evidence. A total of 15 RCTs involving 43,875 patients were included. DP-DES was associated with significantly lower major bleeding rates compared to BP-DES (RR 0.44, Crl 0.22–0.83) in short-term DAPT. Among DP-DES patients, short-term DAPT was associated with lower major bleeding risk compared to standard DAPT (RR 0.47, CrI 0.32–0.69). This favorable bleeding profile with short DAPT was not found in BP-DES patients. Cardiac death, MI, definite stent thrombosis, stroke and TVR rates were similar across the various DAPT durations and stent types. Our preliminary findings demonstrated comparable efficacy and safety outcomes between BP-DES and newer generation BP-DES across various DAPT durations. In patients requiring short DAPT, DP-DES had more favourable major bleeding profile compared to BP-DES, without compromising anti-thrombotic efficacy.